Pre-hatching social interactions mediated by acoustic signals. Dynamics of click emission and hatching synchronization in birds - Florencia Bazterrica; Juan Mateo Mayol; Estefano Vignetta; Vladimir Flores; Melina Rapacioli (PLoS ONE, 2025)
The present paper analyzes the sounds emitted by pre-hatching chicks, focusing on those named as “clicks,” which are thought to mediate pre-hatching social interactions and hatching synchronization. Representative acoustic signals were analyzed under three incubation conditions: (1) isolated pre-hatching chicks (n = 13), (2) pre-hatching chicks in contact with others of the same age (n = 14), and (3) pre-hatching chicks in contact with other of different age (n = 10 for each group: leader and follower). Customized MATLAB software was developed to (a) identify and isolate clicks from other recorded sounds, (b) represent them as temporal series of stochastic point processes, and (c) determine whether click emission dynamics resembled white noise or exhibited characteristics of informative signals. Mathematical methods were applied to analyze (a) temporal dynamics, (b) clustering patterns (via hierarchical clustering and log–log scaling), and (c) scaling properties (via power spectral density analysis) of clicks under each condition. The results reveal developmental-dependent changes in click temporal patterns. As hatching approaches, clicks evolve from isolated events to highly organized hierarchical clusters. Contacting chicks displayed greater temporal organization than isolated ones. Significantly, contact with more advanced chicks accelerated click dynamics in less developed embryos, while older embryos showed a slight delay, suggesting reciprocal social interactions. Spectral analysis revealed long-range correlations consistent with fractional Gaussian noise. These findings confirm that click sequences (a) exhibit physical characteristics of informative signals, (b) function as communication signals, and (c) align developmental processes among pre-hatching chicks. The study underscores the value of fractal analysis in describing physiological signals and expands our understanding of prenatal social interactions. The results suggest that acoustic signals may influence both hatching coordination and central nervous system development. This work provides insight into the evolutionary advantage of embryo communication and highlights the importance of studying how environmental disruptions may affect these critical prenatal processes.